Effects of helium and deuterium irradiation on SPS sintered W–Ta composites at different temperatures - Mateus, R. (2014)
Energetic He+ and D+ ions were implanted into different W–Ta composites in order to investigate their stability under helium and deuterium irradiation. The results were compared with morphological and chemical modifications arising from exposure of pure W and Ta. Special attention was given to tantalum hydride (Ta2H)formation due to its implications for tritium inventory. Three W–Ta composites with 10 and 20 at.% Ta were prepared from elemental W powder and Ta fibre or powder through low-energy ball milling in argon atmosphere. Spark plasma sintering (SPS) was used as the consolidation process in the temperature range from 1473 to 1873 K. The results obtained from pure elemental samples and composites are similar. However, Ta2H is easily formed in pure Ta by using a pre-implantation stage of He+, whereas in W–Ta composites the same reaction is clearly reduced, and it can be inhibited by controlling the sintering temperature.